Breastfeeding and time of complementary food introduction as predictors of obesity in children - Škledar, Mariana Turčić; Milošević, Milan (Central European journal of public health, 2015)
Although obesity is a multifactorial disorder caused by various behavioural, genetic and environmental influences, early life factors affecting certain critical periods during childhood (prenatal period, adiposity rebound period at 3-5 years and around 5-7 years, as well as puberty) are important in promoting obesity in adulthood. The objective was to determine the association between the birth weight, birth length, breastfeeding and time of introduction of complementary food with obesity among 302 healthy Caucasian children 6-7 years old. Binary logistic regression analysis was used to assess the impact of a number of perinatal and socioeconomic confounding factors on the likelihood for overweight and obesity among children. The level of significance was set at p <0.05. Our findings indicate that duration of breastfeeding for at least 3 months, with introduction of complementary food after the age of 6 months have an important role in preventing obesity. This findings are crucial for planning preventive strategies to prevent further increases in the prevalence of overweight and obesity.
Keywords: index tělesné hmotnosti; běloši; mužské pohlaví; Pediatric Obesity; Breast Feeding; Body Mass Index; dítě; Child; logistické modely; Child, Preschool; ženské pohlaví; Humans; předškolní dítě; kojení; Logistic Models; White People; Female; obezita dětí a dospívajících; lidé; Male